2022
DOI: 10.1128/msystems.01253-21
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing Reveals that the Assembly of Functional Genes and Taxa Varied Highly and Lacked Redundancy in the Earthworm Gut Compared with Soil under Vanadium Stress

Abstract: Metagenomic sequencing revealed the variation of functional genes in the microbial community in soil and earthworm gut with increasing vanadium concentrations, which provided a new insight to explore the effect of vanadium stress on microbial community assembly from the perspective of functional genes. Our results reinforced the view that functional genes and taxa do not appear to have a simple corresponding relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Numerous studies suggested that microbial function significantly influences the functions and responses of microbiota, making it a more reliable predictor of community perturbations (Burke et al, 2011). However, our study highlights a dissociation between taxonomic and functional diversity, indicating functional redundancy in the community (Fernandez-Gonzalez et al, 2016;Louca et al, 2018;Xia et al, 2022). Notably, genes in the primary metagenome pool exhibit insensitivity to taxonomic changes, especially those vital for basic metabolisms like heavy metal resistance and nutrient metabolisms (Peter et al, 2011;.…”
Section: Speculative Survival Strategies Adopted By Soil Microorganis...mentioning
confidence: 70%
See 1 more Smart Citation
“…Numerous studies suggested that microbial function significantly influences the functions and responses of microbiota, making it a more reliable predictor of community perturbations (Burke et al, 2011). However, our study highlights a dissociation between taxonomic and functional diversity, indicating functional redundancy in the community (Fernandez-Gonzalez et al, 2016;Louca et al, 2018;Xia et al, 2022). Notably, genes in the primary metagenome pool exhibit insensitivity to taxonomic changes, especially those vital for basic metabolisms like heavy metal resistance and nutrient metabolisms (Peter et al, 2011;.…”
Section: Speculative Survival Strategies Adopted By Soil Microorganis...mentioning
confidence: 70%
“…Previous studies indicate that enriched functional genera enhance the abundance of corresponding genes, facilitating the V(V) reduction process (C. He et al., 2021; B. Zhang, Cheng, et al., 2019). Conversely, no correlation is established between taxonomic diversity and functional diversity in V(V)‐reducing soil communities due to functional redundancy (Xia et al., 2022). Metagenomic analysis, as a culture‐independent tool, captures the full spectrum of potential functional attributes within microbial communities, enhancing our understanding of the specific bacterial functional contributions to V detoxification (Fierer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The migration rate is the movement of species from a hypothetical species pool to a specific environment ( 33 ). The gradual decrease in bacterial taxa migration in response to OCP exposure indicated that the dispersal limitation decreased the significance of the stochastic process in the microbial assembly pattern in OCP-contaminated soil ( 34 ), which was consistent with the NST results.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus, Kluyvera georgiana, Pimelobacter simplex, and Agromyces f lavus in the earthworm gut carry genes related to nitrate/ sulfate reduction, cysteine metabolism, and genes encoding ABC transporters, metal efflux pumps, and antioxidant enzymes, which are likely responsible for V transformation and resistance. 193 Ascidians are known V bioaccumulators in the ocean, and the V concentration in the blood cells of Ascidia gemmata can reach 350 mM (10 7 times that in seawater). V(III) is the main speciation compared to V(V) in seawater, indicating V(V) reduction during its assimilation and hyperaccumulation by ascidians.…”
Section: T H Imentioning
confidence: 99%
“…Furthermore, gut microbes help fauna survive V stress through detoxification and tolerance. Staphylococcus aureus , Kluyvera georgiana , Pimelobacter simplex , and Agromyces flavus in the earthworm gut carry genes related to nitrate/sulfate reduction, cysteine metabolism, and genes encoding ABC transporters, metal efflux pumps, and antioxidant enzymes, which are likely responsible for V transformation and resistance …”
Section: Bioremediation Strategiesmentioning
confidence: 99%